Constraints and Opportunities for MSME Development in Mojokerto Regency : Macroeconomic Perspective - Septyan Budy Cahya; Waspodo Tjipto Subroto; Norida Canda Sakti (International Forum of Researchers and Lecturers, 2025)
This study aims to identify obstacles and opportunities in the development of Micro, Small, and Medium Enterprises (MSMEs) in Mojokerto Regency, Indonesia from a macroeconomic perspective. Using the Systematic Literature Review (SLR) method, this study analyzes various literature and secondary data from national and international sources. The research findings show that MSMEs in Mojokerto Regency face several major obstacles, including limited access to financing, lack of digital literacy, inadequate infrastructure, and challenges in improving the quality of human resources. On the other hand, there are significant opportunities for MSME development through the use of digital technology, government policy support, and export market development. From a macroeconomic perspective, the success of MSME development in Mojokerto will not only have an impact on improving the welfare of local communities but can also contribute to regional and national economic growth. Recommendations from this study include increasing access to financing, accelerating the development of digital infrastructure, and strengthening the capacity of MSME actors through entrepreneurship training and technological literacy. By overcoming these obstacles and utilizing existing opportunities, MSMEs in Mojokerto Regency have the potential to become a driving force for a stronger and more sustainable economy.